Rancang Bangun Sistem Import dan Transformasi Data Excel ke Database Mysql pada Koperasi Syariah Benteng Mikro Indonesia - Erick Tarantino; Farizi Ilham; Pipin Haeriyanti; Tijan Daruri (Router : Jurnal Teknik Informatika dan Terapan, 2026)
Koperasi Syariah Benteng Mikro Indonesia is a microfinance institution that manages member data, financing, and financial transactions. Currently, data processing is still largely conducted using unstructured Excel files, which often leads to data duplication, formatting errors, information inconsistency, and delays in database integration. The objective of this internship project is to design and develop a web-based system for importing and transforming Excel data to improve efficiency, accuracy, and consistency in data management.The development method uses the SDLC Waterfall model, which consists of analysis, design, implementation using Python Flask and MySQL, and testing. Data collection methods include interviews, observations, and literature studies involving administrative staff and the IT division of the cooperative.The system scope includes eight main features: (1) Excel file upload; (2) data preview; (3) interactive column mapping; (4) automatic data validation; (5) data format transformation; (6) import process simulation; (7) data import into a MySQL database; and (8) logging and reporting of import results.The expected outcomes are to reduce data errors by up to 85%, accelerate data entry processes, improve database consistency, and support structured and integrated digitalization of cooperative data.